Relationship of serum estradiol and progesterone with symptoms and sex difference in schizophrenia: A cross-sectional study in Iran - Shahini, Najmeh; Salimi, Zanireh; Kiani, Dorsa; Raftari, Ahmad; Ziaee, Maliheh (Frontiers in Psychiatry, 2023)
Background: Schizophrenia is a devastating disease characterized by frequent relapses, cognitive decline, and emotional and functional disability, with unknown causes. The phenomenology and clinical course of schizophrenic disorders are different between the two genders, which is thought to be related mainly to the effects of steroid sex hormones on the nervous system. Regarding inconsistencies in the studies, we aimed to compare the levels of estradiol and progesterone between schizophrenia patients and healthy individuals. Methods: This case-control study was conducted on 66 patients referred to the specialized clinical psychiatric wards of a teaching hospital in the north of Iran, for five months in 2021. Thirty-three schizophrenia patients confirmed by a psychiatrist based on DSM5 criteria were included in the case group, and 33 individuals without a psychiatric disease, matched for age and sex, were included in the control group. We completed a demographic information checklist for each patient, along with the Simpson-Angus Extrapyramidal Side Effect Scale (SAS) for drug side effects and The Positive and Negative Syndrome Scale (PANSS) for the severity of the disease symptoms. Then, a 3-mL blood sample was taken from each participant to determine the serum levels of estradiol and progesterone. The data were analyzed by SPSS16 software. Results: Thirty-four (51.5%) and 32 (48.5%) participants in this study were male and female, respectively. The mean serum level of estradiol was 22.33 ± 13.65 pm/dL in schizophrenia patients and 29.36 ± 21.32 pm/dL in the control group, showing no significant difference between the two groups (P=0.4). However, the mean serum level of progesterone was significantly lower in schizophrenia patients (0.37±1.39pm/dl) than in control subjects (3.15±5.73pm/dl) (P<0.001). The PANSS and SASS scores were not significantly correlated with the level of sex hormones (P>0.05(. Serum estradiol and progesterone levels based on sex significantly differed between the two groups (except for female estradiol). Conclusion: Considering the hormonal differences between schizophrenia patients and control subjects, determining hormonal levels in these patients and using complementary hormonal therapies with estradiol or similar compounds can be beneficial as the starting point of schizophrenia treatment, where therapeutic responses can draw the future developmental framework.